A Method to Determine Moment Magnitudes of Large Earthquakes Based on the Long‐Period Coda - Xinyu Jiang; Xiaodong Song (Geophysical Research Letters)
Abstract We present a novel and robust method for estimating moment magnitudes (Mw) of large earthquakes with long‐period and long‐lasting coda energy. Fitting the energy with a simple decay model, we derive a straightforward relationship between the coda energy and the Mw. Tests with both real and synthetic data of 10 globally distributed large earthquakes (Mw > 8) verify the method and the results are stable and reliable even with a fast calculation of synthetics for a 1D model. Tests also show that the method is applicable for earthquakes with Mw above 7.5–8.0 with energy sufficiently greater than the ambient noise. The method removes or reduces the effects of geometric spreading, focal mechanism, source rupture process, and the actual Earth structure, making it advantageous for estimating the magnitudes of large earthquakes. The new long‐period coda moment magnitude (Mwo) estimations are similar to the conventional solutions but are slightly larger (by 0.04 on average).